Greece : Fourth Review Under the Stand-By Arrangement and Request for Modification and Waiver of Applicability of Performance Criteria. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2011)
This study is carried out against a backdrop of deep divisions in Greece and in Europe over how to handle the challenges now confronting Greece. Greece's deeper medium-term policy needs and identifying ways to replace the expected market financing are discussed. Structural reforms tackled to strengthen the competitiveness and help the country integrate into the euro area. Finally, Greece has specified the policies necessary to overcome recent inertia and deliver program objectives, and a memorandum of financial and economic policies is discussed.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet